Wall avoiding robot - Mohd Noor, Zamri (2008)
This project is called “wall avoiding robot” which is used to avoid wall or obstacle. To make the robot avoid, ultrasonic sensor is used as an input to the PIC16F877A microcontroller board and two RC servomotors to move the robot. During the robot is move, ultrasonic sensor is ON to detect the obstacle. If the sensor detects the wall or obstacle it will give logic '1' to PIC board. PIC board will stop one of RC servomotor to make the robot TURN. The turn depend on where the position of the robot. If the obstacles are at the right sigh, it will turn to the left. If the obstacles are at the left sigh, it will turn right. It will ON back the RC servomotor if ultrasonic sensor didn't detect obstacle.